- Strategi Pemerintah Desa Dalam Pengelolan Pendapatan Asli Desa Untuk Meningkatkan Pembangunan Desa Tambang Rambang Kecamatan Rambang Kuang Kabupaten Ogan Ilir: - - Puji Lestari, Delfiazi; Rusdi , Rusdi; Risnadewi (Lentera Jurnal Manajemen, 2024)
The aim of this research is to determine the Village Government's Strategy in Managing Village Original Income to improve the Development of Tambang Rambang Village, Rambang Kuang District, Ogan Ilir Regency. Next, to find out the factors that hinder the Village Government's Strategy in Managing Village Original Income to Improve the Development of Tambang Rambang Village, Rambang Kuang District, Ogan Ilir Regency. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques in this research were obtained from observation, interviews and documentation. The data analysis technique for this research involves collecting data, reducing data, presenting data and drawing conclusions. The results of this research show that the Tambang Rambang village government in managing the original income of Tambang Rambang Village, Rambang Kuang District, Ogan Ilir Regency is making every effort to improve village development through optimization strategies, namely identification and inventory of the value and potential of village wealth, the need for a village management information system, supervision and controlling the use of village assets and involvement of appraisal services. The inhibiting factors are the low level of public knowledge, limited competent human resources and lack of implementation of information systems, but the management of the original income of Tambang Rambang Village is running well. Suggestions from the results of this research in managing village original income to improve the development of Tambang Rambang Village, Rambang Kuang District, Ogan Ilir Regency need to be further optimized.